2019
DOI: 10.1002/jat.3910
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological study of metal and metal oxide nanoparticles in zebrafish

Abstract: Metal and metal oxide nanoparticles have been widely used in catalytic, electronic and biomedical fields. It is necessary to investigate their toxicity and potential hazards to human and aquatic ecosystems. Zebrafish (Danio rerio), as a promising animal model, has been increasingly utilized to assess the toxicity of nanoparticles. Zebrafish has numerous characteristics for toxicity evaluation, such as short life cycle and high fecundity. This review describes the advantages of using zebrafish in the toxicity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 221 publications
2
80
1
Order By: Relevance
“…Moreover, histological analysis and a study on the gene expression showed a delay in folliculogenesis (maturation of the ovarian follicle), as well as changes in the maturation and function of the ovaries of fish exposed to TiO 2 NPs. Thus, it has been confirmed once more that these nanoparticles can be toxic at the level of the reproductive system of this species [119].…”
Section: Titanium Dioxide Nanoparticlesmentioning
confidence: 73%
See 2 more Smart Citations
“…Moreover, histological analysis and a study on the gene expression showed a delay in folliculogenesis (maturation of the ovarian follicle), as well as changes in the maturation and function of the ovaries of fish exposed to TiO 2 NPs. Thus, it has been confirmed once more that these nanoparticles can be toxic at the level of the reproductive system of this species [119].…”
Section: Titanium Dioxide Nanoparticlesmentioning
confidence: 73%
“…These results suggest that the contamination of aquatic environments with TiO 2 NPs, even at low doses, may have an impact on the reproduction of species [121]. The effect should constitute another reason for investigation the potential impact of TiO 2 NPs on the environment and the human health [119].…”
Section: Titanium Dioxide Nanoparticlesmentioning
confidence: 83%
See 1 more Smart Citation
“…[5,11] Several recent reviews provide an excellent overview of the mechanisms of nano-TiO 2 toxicity and highlight the potential for adverse health effects of nano-TiO 2 requiring further research and improved regulatory practices. [10,[12][13][14][15] However, a comprehensive assessment of the adverse impacts of nano-TiO 2 requires quantitative approaches that can objectively summarize the results of multiple studies and assess the relative importance of different biological responses in the context of the environmentally relevant nano-TiO 2 exposures. Meta-analysis and bibliometric analysis can provide such quantitative approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles (NPs) can be toxic to aquatic organisms, and the mechanism of toxicity may be related to the release of toxic metal ions, unique properties of the NPs, or a combination of effects. The dissolution of ions from metal NPs varies with the type of NP, and TiO 2 -NPs do not appreciably dissolve while others such as Zn-NPs, Ag-NPs, Cu-NPs, and CuO-NPs can release sufficient amounts of metal ions to cause acute toxicity in fishes (Bai and Tang, 2020;Shaw and Handy, 2011;Thit et al, 2017). Cu-NPs are used widely in industrial applications (Cioffi et al, 2005;Liu et al, 2004) and include various forms (e.g.…”
Section: Introductionmentioning
confidence: 99%